Enhancing credibility and commitment to fiscal rules - Grzegorz Poniatowski (Center for Social and Economic Research (CASE), 2018)
The objective of this paper is to derive the characteristics of an effective fiscal governance framework, focusing on the incentives that ensure a commitment to the fiscal rules. We study this problem with the use of econometric tools, complementing this analysis with formal modelling through the lens of a dynamic principal-agent framework. Our study shows that both economic and institutional factors play an important role in incentivising countries' fiscal efforts. Fiscal balances are affected not only by the economic cycle, but, among others, by the level of public debt and the world economic situation. We find that the existence of numerical fiscal rules, their strong legal entrenchment, surveillance mechanisms, and credible sanctions binding the hands of governments have a significant impact on curbing deficits. The relationship between the Commission and European Union (EU) Member States (MS), where the EU authorities act as a collective principal that designs contracts for MS, has elements in common with the assumptions of the principal-agent framework. These are: asymmetry of information, moral hazard, different objectives, and the ability to reward or punish the principal. We use a dynamic principal-agent model and show that to ensure good fiscal performance, indirect benefits should be envisaged for higher levels of fiscal effort. In order to account for the structural differences of exerting effort by different MS, it is efficient to adjust fiscal effort to the level of indebtedness. To ensure a commitment to the rules, MS with difficulties conducting prudent fiscal policies should be required to exert less effort than the MS with more modest levels of debt.
Keywords: D82; E61; H60; 330; Principal-Agent; Moral Hazard; Fiscal Effort; Fiscal Rules; Cyclically-Adjusted Balance